Does serum angiotensin converting enzyme reflect intensity of alveolitis in sarcoidosis?. Issue 7 (July 1985) - Cohen, R D; Bunting, P S; Meindok, H O; Chamberlain, D W; Rebuck, A S
Abstract : Serum angiotensin converting enzyme activity is increased in many patients with pulmonary sarcoidosis and has been proposed as a measure of disease activity. Assay of serum angiotensin converting enzyme, bronchoalveolar lavage, and gallium scans were performed in 27 patients with biopsy proved pulmonary sarcoidosis. There was a positive correlation between serum angiotensin converting enzyme activity and an index of pulmonary gallium uptake assessed by the National Institutes of Health method (r = 0.7, p less than 0.001). There was no significant relationship (r = 0.19) between serum angiotensin converting enzyme activity and bronchoalveolar lavage lymphocytes expressed as a proportion of cells recovered. Increase in the enzyme activity had a sensitivity of 50% as a means of detecting high intensity alveolitis but specificity was only 45%. There was no significant difference in mean angiotensin converting enzyme activity between the following groups: those with positive and those with negative gallium scans; those with bronchoalveolar lavage lymphocyte counts less than or equal to 28% and those with counts greater than 28%. Although there was a significant correlation between the enzyme activity and one component of the alveolitis of sarcoidosis, the data suggest that serum angiotensin converting enzyme activity alone is neither sensitive nor specific enough for high intensity alveolitis.